McGraw-Hill dictionary of scientific and technical terms (McGraw-Hill, 2003)
The "McGraw-Hill Dictionary of Scientific and Technical Terms" is famous for its broad-spectrum coverage. Its soul is general science; and its audience is anybody who has any business with any science: biological, chemical, or physical. Whether you are a student, a teacher, or even a consultant, this unabridged lexicon lets you discover scientific terms, methods and applications in a very simple way. It is overflowing with references and definitions.